Higher helminth ova counts and incomplete decomposition in sand-enveloped latrine pits in a coastal sub-district of Bangladesh. - Mahbubur Rahman; Mahfuza Islam; Solaiman Doza; Abu Mohammed Naser; Abul Kasham Shoab; Julia Rosenbaum; Md Shariful Islam; Leanne Unicomb; Thomas F Clasen; Ayse Ercumen (Public Library of Science (PLoS), 2022)
Pit latrines are the most common latrine technology in rural Bangladesh, and untreated effluent from pits can directly contaminate surrounding aquifers. Sand barriers installed around the latrine pit can help reduce contamination but can also alter the decomposition of the fecal sludge and accelerate pit fill-up, which can counteract their benefits. We aimed to evaluate whether there was a difference in decomposition of fecal sludge and survival of soil-transmitted helminth (STH) ova among latrines where a 50-cm sand barrier was installed surrounding and at the bottom of the pit, compared to latrines without a sand barrier, in coastal Bangladesh. We assessed decomposition in latrine pits by measuring the carbon-nitrogen (C/N) ratio of fecal sludge. We enumerated Ascaris lumbricoides and Trichuris trichiura ova in the pit following 18 and 24 months of latrine use. We compared these outcomes between latrines with and without sand barriers using generalized linear models with robust standard errors to adjust for clustering at the village level. The C/N ratio in latrines with and without a sand barrier was 13.47 vs. 22.64 (mean difference: 9.16, 95% CI: 0.15, 18.18). Pits with sand barriers filled more quickly and were reportedly emptied three times more frequently than pits without; 27/34 latrines with sand barriers vs. 9/34 latrines without barriers were emptied in the previous six months. Most reported disposal methods were unsafe. Compared to latrines without sand barriers, latrines with sand barriers had significantly higher log10 mean counts of non-larvated A. lumbricoides ova (log10 mean difference: 0.35, 95% CI: 0.12, 0.58) and T. trichiura ova (log10 mean difference: 0.47, 95% CI: 0.20, 0.73). Larvated ova counts were similar for the two types of latrines for both A. lumbricoides and T. trichiura. Our findings suggest that sand barriers help contain helminth ova within the pits but pits with barriers fill up more quickly, leading to more frequent emptying of insufficiently decomposed fecal sludge. Further research is required on latrine technologies that can both isolate pathogens from the environment and achieve rapid decomposition.